ANALISIS LAPORAN KEUANGAN SEBAGAI EVALUASI KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN HALMAHERA TENGAH - Ramdani, Muhammad Reza (Jurnal Riset Akuntansi (JUARA), 2019)
This study examines the financial performance of the Central Halmahera government through the analysis of financial statement assessments. The purpose of this study was to determine the financial performance of the Central Halmahera Government. This research approach uses a quantitative approach. The source of data in this study is from the Central Halmahera Government Financial Report. Research data collection techniques with observation and desk study of reports or archives. The method of analysis uses descriptive by calculating the formula of regional financial independence ratio, Debt services cavarage ratio (DSCR), the ratio of effectiveness and efficiency of local revenue results, activity ratios, growth ratios and liquidity ratios. The results showed the ability of the Central Halmahera District Government in financing government activities and development and community services was still relatively low and still needed funding assistance or loans from external parties.